2017
DOI: 10.5194/bg-14-2225-2017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxides and ozone fluxes from an oilseed-rape management cycle: the influence of cattle slurry application

Abstract: Abstract. This study reports NO, NO2 and O3 mixing ratios and flux measurements using the eddy covariance method during a 7-month period over an oilseed-rape field, spanning an organic and a mineral fertilisation event. Cumulated NO emissions during the whole period were in agreement with previous studies and showed quite low emissions of 0.26 kg N ha−1 with an emission factor of 0.27 %, estimated as the ratio between total N emitted in the form of NO and total N input. The NO emissions were higher following o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…In the actual work, the universal function for heat H,(z−d)/L as published by Businger (1966) was integrated with the method of Dyer and Hicks (1970) for the unstable case. For the stable case the universal function for heat as published by Webb (1970) was used (see Supplement). The flux of a scalar, which is equal to u * · χ * , can be deduced from Eq.…”
Section: Aerodynamic Gradient Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the actual work, the universal function for heat H,(z−d)/L as published by Businger (1966) was integrated with the method of Dyer and Hicks (1970) for the unstable case. For the stable case the universal function for heat as published by Webb (1970) was used (see Supplement). The flux of a scalar, which is equal to u * · χ * , can be deduced from Eq.…”
Section: Aerodynamic Gradient Methodsmentioning
confidence: 99%
“…This site, operated by INRA (Institut National de la Recherche Agronomique) and hosted by AgroParisTech, was part of the EC CarboEurope-IP, NitroEurope-IP, Eclaire-IP and INGOS-IP European projects and is part of the ICOS and Fluxnet measurement networks. The site is well documented (Laville et al, 2009;Loubet et al, 2011) as are several experiments on reactive trace gases performed at the site (Bedos et al, 2010;Loubet et al, 2012Loubet et al, , 2013Potier et al, 2015;Personne et al, 2015;Wu et al, 2016;Vuolo et al, 2017). Briefly, measurements were carried out on a 19 ha field with a fetch of 100-400 m depending on wind direction.…”
Section: Field Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of NO-NO 2 -O 3 chemistry to observed ozone fluxes can be estimated with ozone, NO, and NO 2 fluxes at two heights (Finco et al, 2018;Fitzjarrald & Lenschow, 1983;Lenschow & Delany, 1987;Vilá-Guerau de Arellano et al, 1993). An empirical technique only requiring flux measurements at one height has also been used (e.g., Plake, Sörgel, et al, 2015;Stella et al, 2012;Vuolo et al, 2017). This empirical technique assumes flux divergences of NO, NO 2 , and ozone are logarithmic with height, but the theoretical basis for this assumption is lacking.…”
Section: Fast Ambient Chemistrymentioning
confidence: 99%
“…Mechanisms behind the chemical quenching at the soil surface are not completely understood but findings from several flux partitioning studies emphasized the soil as an important sink for O 3 in forests (Lamaud et al, 2002;Dorsey et al, 2004;Fares et al, 2014;Zhou et al, 2017) as well in ecosystems with smooth surfaces (Sanchez et al, 1997;Meszaros et al, 2009;Stella et al, 2013). The fact that low ground water levels favored O 3 uptake suggested that the depth or soil volume available for O 3 to diffuse in the soil pores constituted a limiting factor for uptake in the soil Vuolo et al, 2017). A laboratory study, conducted by Sorimachi and Sakamoto (2007) on Chinese soil samples revealed that there was only a small impact of geometric surface area or soil weight on υ d .…”
Section: Drivers Of Non-stomatal Depositionmentioning
confidence: 99%